Several Dimensions of Innovation, Technology and Industry 4.0 - Ayhan, Fatih (Peter Lang GmbH, Internationaler Verlag der Wissenschaften, 2019)
With the development of the industry, both social lives and economies have been significantly affected. Together with the Industry 4.0 revolution, significant changes have occurred in both the social life and the production process. As a result, different sectors are affected by this change. With this book, successful researches have been carried out by expert academics in a wide range of fields from finance to marketing and tourism to foreign trade, etc.